Bridging agricultural gaps through experience: evaluating conservation attitudes among youth and hydroponics learning outcomes among interns - Carpenter, Charles Wayne III (My University, 2025)
Many urban and minority youth have little exposure to sustainable crop production and therefore have a minor understanding of the importance and various practices used in conserving natural resources. To combat this knowledge discrepancy, the Student and Staff Success Office (SSSO) at Kansas State University has hosted Junior MANRRS groups since 2021 to expose youth to different facets of agriculture and provide hands-on/experiential learning opportunities. During the summer of 2024, the KSU Switzer-Nicodemus educational camp was hosted in partnership with Willow Lake Student Farm, engaging 25 minority youth (ages 7–17). Activities introduced participants to soil and water conservation practices to improve awareness, understanding, and attitudes toward natural resource conservation within crop production. Participants completed pre- and post-assessments, including Likert-scale and open-ended questions, as well as a nine-question multiple choice worksheet to evaluate learning outcomes. Results indicated that campers demonstrated improved agricultural knowledge and increased awareness of sustainability following lectures and hands-on experiences, with urban youth showing the greatest gains. This thesis also investigates the impact of hydroponics instruction on undergraduate students participating in a Research and Extension Experiences for Undergraduates (REEU)-sponsored internship program. With growing global food demands and limited arable land, hydroponic systems represent an innovative solution to sustainable crop production. However, barriers such as technical complexity and limited educational exposure hinder adoption. This study explores how structured learning—including a lecture and hands-on hydroponic workshop—affects students’ agricultural knowledge, perceptions, and confidence. Pre-, post-, and follow-up surveys showed statistically significant gains, particularly among students who received hands-on instruction. The findings support experiential learning as a critical tool in building understanding and confidence in both youth and undergraduate populations, while highlighting the importance of integrating experiential approaches into agricultural education to address knowledge gaps and prepare future leaders in sustainable agriculture.
Keywords: Experiential learning; Sustainable agriculture; Hydroponics education; Natural resource conservation; Minority youth